TINGKAT KEBUGARAN JASMANI ATLET HOKI INDOOR STKIP PASUNDAN CIMAHI - Hidayat, Yudi (Jurnal Olahraga, 2019)
The purpose of this study was to determine the level of physical fitness of hockey athletes from STKIP Pasundan Cimahi 2017. The research method used was descriptive survey method. The population and sample of this study were 2016 Hockey STKIP Pasundan Cimahi 2016 athletes who actively practiced 14 people, and the sampling technique used total sampling. The instrument used was a physical condition test, namely: Modified Sit and Reach, Sit-Up, Shuttle Run, 20 meter run, Bleep Test and Vertical Jump. The results showed: 1) None of the 2017 STKIP Pasundan Cimahi hockey athletes were categorized as Excellent and Good; 2) There are six or 43% of hockey athletes in STKIP Pasundan Cimahi that fall into the Fair category; 3) There are six or 43% of hockey athletes in STKIP Pasundan Cimahi that fall into the Poor category; 4) There are two or 14% of hockey athletes in STKIP Pasundan Cimahi which are in the Very Poor category. Overall it can be concluded that the fitness level of hockey athletes in STKIP Pasundan Cimahi in 2017 is in the category of Less